Editorial - Schilling , Angela; Lymn , Jessie (Archives & Manuscripts, 2024)
This issue concludes the 2023 publishing year, albeit published in 2024 due to the unpredictability of many elements that come together to make a society journal, including managing the time demands of authors and peer reviewers, Editor and production team changes and availability, and at times, the general pace of life in these current times which means over-commitments, juggling multiple hats and roles, and the nature of human life. Thanks to the move to a Society-based publishing model, however, we have been able to publish all the articles in this issue ‘online first’ as they are finalised, allowing authors to disseminate their findings and experiences as soon as possible. As always, online first articles are available from the Archives and Manuscripts website at publications.archivists.org.au